2015
DOI: 10.1002/anie.201507004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Dehydrocoupling: Group 2 Mediated Boron–Nitrogen Desilacoupling

Abstract: The alkaline-earth element bis(trimethylsilyl)amides, [Ae{N(SiMe3 )2 }2 (thf)2 ] [Ae=Mg, Ca, Sr], are effective precatalysts for boron-nitrogen bond formation through the desilacoupling of amines, RR'NH (R=alkyl, aryl; R'=H, alkyl, aryl), and pinBSiMe2 Ph. This reactivity also yields a stoichiometric quantity of Me2 PhSiH and provides the first example of a catalytic main-group element-element coupling that is not dependent on the concurrent elimination of H2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…We have recently reported that reaction of the silylborane pinBSiMe 2 Ph with the β-diketiminato magnesium n -butyl derivative [HC{(Me)CN(Dipp)} 2 Mg n- Bu] (7) provides ready access to the magnesium silyl species [HC{(Me)CN(Dipp)} 2 MgSiMe 2 Ph] ( 8 ) through elimination of a n- BuBpin by-product46. This reaction was envisaged to ensue via a four-membered σ-bond metathesis transition state, the assembly of which was facilitated by the relative polarity of the Mg–C and Si–B bonds and the ability of boron to increase its coordination number in a β-position to the magnesium centre.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that reaction of the silylborane pinBSiMe 2 Ph with the β-diketiminato magnesium n -butyl derivative [HC{(Me)CN(Dipp)} 2 Mg n- Bu] (7) provides ready access to the magnesium silyl species [HC{(Me)CN(Dipp)} 2 MgSiMe 2 Ph] ( 8 ) through elimination of a n- BuBpin by-product46. This reaction was envisaged to ensue via a four-membered σ-bond metathesis transition state, the assembly of which was facilitated by the relative polarity of the Mg–C and Si–B bonds and the ability of boron to increase its coordination number in a β-position to the magnesium centre.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] TheM g À Si interaction of 2.6022(9) is slightly longer than that reported for 1 of 2.5900 (7) . [18] Due to difficulty in isolation, anumber of these species were isolated as solvates containing coordinating ethers. 2a·THF and 4a·OEt 2 exhibit longer MgÀSi bonds (2.614(1) and 2.664(3) respectively) than 1,consistent with the higher coordination number at Mg.…”
mentioning
confidence: 71%
“…A number of lithium and magnesium silyls were synthesized . Magnesium silyl reagents ( 1 – 4 ) were prepared by a two‐step procedure involving sequential deprotonation of the pro‐ligand (β‐diketiminate, iminoanilide or guanidine) with [Mg n/s Bu 2 ] followed by a metathesis reaction with R 3 Si‐Bpin (Figure ) . In an alternative approach, lithium silyls ( 5⋅THF , 5⋅TMEDA, 5⋅PMDETA ) were synthesised by direct metalation of PhMe 2 SiCl with Li metal (Figure ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[8] We reasoned that this apparently limited onward reactivity was al ikely consequence of the sterically demanding ORTEP representation (25 %thermal ellipsoids) of 2 with hydrogen atoms removed for clarity. [9] Selected bond lengths [] and angles [8 8]: Mg-N2 2.0128(13), Mg-N1 2.0173(13),M g-Si 2.5900 (7), N2-Mg-N19 3.40 (5), N2-Mg-Si 130.76 (4), N1-Mg-Si 135.81 (4).…”
mentioning
confidence: 99%